PENGARUH SERVICE QUALITY TERHADAP CUSTOMER BEHAVIORAL INTENTION DENGAN MEDIASI CUSTOMER SATISFACTION - Benhardo Chandra; Rita Rita (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
Fivestar Reflexology branch Meruya located in West Jakarta is one of the hospitality industries which is owned by PT Panca Abadi Bersama that provides breakthrough of healthy and relaxation. The basic objective of this research is to determine the influence service quality to customer behavioral intention through customer satisfaction on Fivestar Reflexology branch Meruya. The method used in this study is the path analysis. The result shows that service quality has significant effect on customer satisfaction. Subsequent findings, found that service quality was also has direct and positive effect on customer behavioral intention. From these results, it was found that the implementation of service quality on customer behavioral intention through the mediation customer satisfaction is more influential than directly.